METODE PENGENALAN POLA TRABEKULA MANDIBULA PADA RADIOGRAF PERIAPIKAL DIGITAL UNTUK DETEKSI DINI RISIKO OSTEOPOROSIS - Sri Lestari dan Evrita Lusiana Utari (Universitas Gadjah Mada, 2013)
Osteoporosis is a sistemic skeletal disease. Osteoporosis examination using the gold standard determined byWHO, namely DEXA, is relatively expensive and the result can not show the bone microarchitecture. Meanwhile,the probability of advanced age women to visit a dentist is relatively high. If the condition of bone mass densitywhich indicate osteoporotic condition can be recognized from the trabecullar pattern of mandible, so the dentistcan participate in early detection of a patient having a risk of osteoporosis. The objective of this research is to getthe pattern recognition method which can be applied to digital periapical radiograph that characterize the bonemass density condition. Combination of Sobel’s edge detection with the binary image has been applied to the image,producing an image showing the mandible trabecullar pattern visually. Supported by fractal dimension value andfind local maxima in the binary image, the pattern can be better distinguished for each condition of osteoporosis,osteopenia, and normal. The value of fractal dimension and find maxima is positively correlated with the bonemass density.